The Influence of Live Streaming, Online Customer Reviews, and Discounts on Impulse Buying Behavior on Tiktok Shop in Bali - Ni Putu Surya Maharani; Putu Ngurah Suyatna Yasa; Made Setini (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
The rapid growth of social commerce platforms has significantly transformed consumer purchasing behavior, particularly in the beauty product industry. This study aims to examine the influence of live streaming, online customer reviews, and discounts on impulse buying behavior among TikTok Shop users in Bali. A quantitative research approach was employed using a survey method. Data were collected from 100 respondents who had purchased Glad2Glow products through TikTok Shop using purposive sampling. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The results show that live streaming has a positive and significant effect on impulse buying, indicating that interactive product demonstrations and real-time communication between sellers and consumers can stimulate spontaneous purchasing behavior. Online customer reviews also have a positive and significant influence on impulse buying, as positive and credible reviews increase consumer trust and reduce uncertainty in purchase decisions. In addition, discounts were found to significantly influence impulse buying behavior by creating a perception of higher value and a sense of urgency among consumers. These findings highlight the important role of digital marketing strategies in shaping consumer purchasing behavior on social commerce platforms. The study provides practical implications for online sellers and digital marketers to optimize live streaming activities, encourage positive customer reviews, and implement effective discount strategies to enhance consumer engagement and increase impulse buying behavior.